Genomic insights into abiotic stress tolerance in polar lichen-associated Sphingomonas sp. PAMC26617 and Sphingomonas sp. PAMC26621 - Anamika Khanal; So-Ra Han; Jun Hyuck Lee; Tae-Jin Oh (Extremophiles, 2026)

Genomic and transcriptomic insights into benzoate and 4-hydroxybenzoate degradation in Arthrobacter sp. PAMC25564 isolated from cryoconite - Nisha Ghimire; Byeollee Kim; So-Ra Han; Jun Hyuck Lee; Tae-Jin Oh (International Biodeterioration & Biodegradation, 2025)

Exploiting CotA laccase from Antarctic Bacillus sp. PAMC28748 for efficient mediator-assisted dye decolorization and ABTS regeneration - Jayram Karmacharya; Prasansah Shrestha; So-Ra Han; Jun Hyuck Lee; Tae-Jin Oh (Chemosphere, 2025)

Complete genome of Nakamurella sp. PAMC28650: genomic insights into its environmental adaptation and biotechnological potential - Lakshan Paudel; Nisha Ghimire; So-Ra Han; Hyun Park; Sang-Hee Jung; Tae-Jin Oh (Functional & Integrative Genomics, 2023)
The mechanisms underlying the survival of bacteria in low temperature and high radiation are not yet fully understood. Nakamurella sp. PAMC28650 was isolated from a glacier of Rwenzori Mountain, Uganda, which species belonged to Nakamurella genus based on 16S rRNA phylogeny, ANI (average nucleotide identity), and BLAST Ring Image Generator (BRIG) analysis among Frankineae suborder. We conducted the whole genome sequencing and comparative genomics of Nakamurella sp. PAMC28650, to understand the genomic features pertaining to survival in cold environment, along with high UV (ultraviolet) radiation. This study highlights the role of polysaccharide in cold adaptation, mining of the UV protection-related secondary metabolites and other related to cold adaptation mechanism through different bioinformatics tools, and providing a brief overview of the genes present in DNA repair systems. Nakamurella sp. PAMC28650 contained glycogen and cellulose metabolism pathways, mycosporine-like amino acids and isorenieratene-synthesizing gene cluster, and a number of DNA repair systems. Also, the genome analysis showed osmoregulation-related genes and cold shock proteins. We infer these genomic features are linked to bacterial survival in cold and UV radiation.

Comparative analysis of genome-based CAZyme cassette in Antarctic Microbacterium sp. PAMC28756 with 31 other Microbacterium species - Sushma Gupta; So-Ra Han; Byeollee Kim; Chang-Muk Lee; Tae-Jin Oh (Genes & Genomics, 2022)

Complete genome sequencing and comparative CAZyme analysis of Rhodococcus sp. PAMC28705 and PAMC28707 provide insight into their biotechnological and phytopathogenic potential - Nisha Ghimire; So-Ra Han; Byeollee Kim; Sang-Hee Jung; Hyun Park; Jun Hyuck Lee; Tae-Jin Oh (Archives of Microbiology, 2021)

Complete Genome Sequence of Pedobacter sp. PAMC26386 and Their Low Temperature Application in Arabinose-containing Polysaccharides Degradation - Cya-Yong Cho; So-Ra Han; Tae-Jin Oh (Current Microbiology, 2021)

Comparative Genomic Study of Polar Lichen-Associated Hymenobacter sp. PAMC 26554 and Hymenobacter sp. PAMC 26628 Reveals the Presence of Polysaccharide-Degrading Ability Based on Habitat - Nisha Ghimire; So-Ra Han; Byeollee Kim; Hyun Park; Jun Hyuck Lee; Tae-Jin Oh (Current Microbiology, 2020)

Complete genome sequence of Sphingobium sp. strain PAMC 28499 reveals a potential for degrading pectin with comparative genomics approach - So-Ra Han; Sung-Min Jang; Young Min Chi; Byeollee Kim; Sang-Hee Jung; Yung Mi Lee; Jun Uetake; Jun Hyuck Lee; Hyun Park; Tae-Jin Oh (Genes & Genomics, 2020)

Air anions improve growth and mineral content of kale in plant factories - So-Ra Lee; Tae-Hwan Kang; Chung-Su Han; Myung-Min Oh (Horticulture, Environment, and Biotechnology, 2015)

Numerical simulation of the heavy rainfall caused by a convection band over Korea: a case study on the comparison of WRF and CReSS - Eun-Soon Im; So-Ra In; Sang-Ok Han (Natural Hazards, 2013)

Esculetin promotes type I procollagen expression in human dermal fibroblasts through MAPK and PI3K/Akt pathways - Jung Hae Park; So Ra Kim; Hyun Ju An; Woo Jin Kim; Myeon Choe; Jeong A. Han (Molecular and Cellular Biochemistry, 2012)

Potential increase of flood hazards in Korea due to global warming from a high-resolution regional climate simulation - Eun-Soon Im; Byong-Ju Lee; Ji-Hye Kwon; So-Ra In; Sang-Ok Han (Asia-Pacific Journal of Atmospheric Sciences, 2012)